Comic Education Media On Food Label With Folklore Character For Children - Almira Sitasari; Andika Trisurini (POLTEKKES KEMENKES YOGYAKARTA, 2018)
Lack of awareness in food label reading could be a problem of eating habit in Indonesian especially in youth. School-aged children are susceptible group to have risk from unsafe packaged snack food. Comic book would be one of good education media for them. Aim of the study was to raise awareness to food label reading and to make a good media to educate youth to read packaged food/snack label. This study was a research and development study (R and D study) with 4 D approach (define, design, develop, disseminate). After designing the media (including storyline and cover design) the media was rated by 2 media experts, tested in school-aged children, and also requested feedback from school teachers. Quantitative data were shown in percentage of feasibility, while qualitative data were analyzed by saturation of data. The rating test from experts showed that overall comic feasibility was 87,86% (means feasible to use). The testing from users or school-aged children showed that overall comic feasibility was 96,41% (means feasible). The school teachers gave positive feedbacks on comic book. The conclusion of the study is that the comic book about food labelling with folklore character is feasible to use.